2021
DOI: 10.21203/rs.3.rs-395007/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ficus deltoidea ameliorates biochemical, hormonal, and histomorphometric changes in letrozole-induced polycystic ovarian syndrome rats

Abstract: Background: Insulin resistance and hormonal imbalances are key features in the pathophysiology of polycystic ovarian syndrome (PCOS). We have shown that Ficus deltoidea var. deltoidea Jack (Moraceae) can improve insulin sensitivity and hormonal profile in PCOS female rats. However, biological characteristics underpinning the therapeutic effects of F. deltoidea for treating PCOS remain to be clarified. This study aims to investigate the biochemical, hormonal, and histomorphometric changes in letrozole (LTZ)-ind… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
2
0
0
Order By: Relevance
“…The present results show elevation in plasma MDA level that is accompanied with reduced glutathione (GSH) level in PCOS group compared with control. This observation is consistent with a recent study in PCOS patients that found elevated circulating MDA (Uçkan et al 2022) and in experimental animals (Haslan et al 2021). Usually, PCOS present with higher levels of blood lipids (Klimczak et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…The present results show elevation in plasma MDA level that is accompanied with reduced glutathione (GSH) level in PCOS group compared with control. This observation is consistent with a recent study in PCOS patients that found elevated circulating MDA (Uçkan et al 2022) and in experimental animals (Haslan et al 2021). Usually, PCOS present with higher levels of blood lipids (Klimczak et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, ovarian SOD, CAT, and total peroxidase concentrations were much lower in PCOS rats, whereas ovarian MDA was significantly greater in PCOS rats, which was consistent with earlier research on PCOS patients [ 86 , 87 ]. In this paradigm, oxidative stress was verified in PCOS rats.…”
Section: Discussionsupporting
confidence: 93%